Immunological Aspects of Acute and Recurrent Herpes Simplex Keratitis. (7th September 2014) - Rolinski, Jacek; Hus, Iwona
Abstract : Herpes simplex keratitis (HSK) belongs to the major causes of visual morbidity worldwide and available methods of treatment remain unsatisfactory. Primary infection occurs usually early in life and is often asymptomatic. Chronic visual impairment and visual loss are caused by corneal scaring, thinning, and vascularization connected with recurrent HSV infections. The pathogenesis of herpetic keratitis is complex and is still not fully understood. According to the current knowledge, corneal scarring and vascularization are the result of chronic inflammatory reaction against HSV antigens. In this review we discuss the role of innate and adaptive immunities in acute and recurrent HSV ocular infection and present the potential future targets for novel therapeutical options based on immune interventions.